In-situ sintering reaction of Al2O3–LaAl11O18–ZrO2 composite. (January 2016) - Naga, S.M.; Hassan, A.M.; El-Maghraby, H.F.; Awaad, M.; Elsayed, Hamada
Abstract: Al2 O3 –LaAl11 O18 –ZrO2 composites were prepared by in situ sintering reaction of different proportions of Al2 O3 and La2 Zr2 O7 . The studied batches were uniaxially pressed and pressureless sintered at 1600 °C up to 1725 °C for 1 h. Phase composition study reveals that the only present phases are alumina, lanthanum hexaluminates and zirconia. No other intermediate phases are present. Rodlike LaAl11 O18 was observed in the sintered bodies containing more than 25 wt.% LaAl11 O18 . The effect of rodlike particles on the densification and mechanical behavior was discussed. It was found that increasing the LaAl11 O18 content more than 25 wt.% enhances the fracture toughness, but reduces both the bending strength and the hardness of the sintered composites. Highlights: In situ sintering reaction between Al2 O3 and La2 Zr2 O7 was performed. The effect of LaAl11 O18 on the mechanical properties of LA6/Al/Zr composite was studied. Formation of LaAl11 O18 rodlike particles affects the densification and mechanical behavior of the composite. Introduction of ZrO2 enhances the behavior of the composite.